Manajemen Peserta Didik di SD: Masalah, Penyebab, dan Alternatif Pemecahannya - Ali Imron (Universitas Negeri Malang, 2016)
The main purpose of this study was to explore problems faced by primary school principals in implementing pupil management. The sample consisted of 60 primary school principals from regions developed by the Primary Education Quality Improvement Project (PEQIP) participating in a management training held in IKIP Malang, 1997. Data were gathered by questionnaire and then verified by a group of peer reviewers. The results showed that problems faced by primary school principals in pupil management were school census, pupil recruitment, pupil orientation, pupil placement, pupil grouping, pupil discipline, guidance and counseling services, pupil evaluation, pupil mutation and school-leaving, and extra-curricular activities